Documenting the archaeological heritage in a museum: the case of the frigate “Nuestra Señora de las Mercedes” in the National Museum of Underwater Archeology ARQVA - Pérez Mateo, Soledad (Revista General de Información y Documentación, 2024)
The analysis of the state of the documentation of the underwater cultural heritage of the ARQVA National Museum of Underwater Archeology makes it possible to identify the priorities, needs and actions aimed at adequate control and management of the collections, documentary, administrative and bibliographic funds. A Documentation Program is proposed to improve the development and management of knowledge in the museum. To this end, documentation priorities are defined, articulated around the cultural asset and its context, the standardization of documentation processes and information structures, the tools used, the  documentary and photographic archive organization, and conservation treatments  with research as the axis the mentioned  Program. We propose the loading of the frigate Mercedes as a case study. Finally, the advantages of controlling and organizing documentary production around underwater cultural heritage are considered, fact which facilitates  the preservation of  information that it holds,  its access and dissemination.
Keywords: Underwater cultural heritage; coins; automated inventory device; Nuestra Señora de las Mercedes frigate; documentation program